Factors influencing job satisfaction and turnover intention among nurses in the UAE - Mohammed Al Maqbali; Muna Al Shehhi; Fatima Al Hosani; Ciara Hughes (PLoS ONE, 2026)
Job satisfaction and turnover intention are critical factors influencing nurse retention and healthcare outcomes. This study explores the impact of organizational policies, work environment, patient care quality, and individual factors on job satisfaction and turnover intention among nurses in the UAE. A cross-sectional survey design was employed, with data collected between August and November 2024 from 313 nurses working across various healthcare settings in the UAE. Validated self-reported questionnaires, including the Job Satisfaction Scale and a Turnover Intention Measure, were used. The survey assessed job satisfaction, turnover intention, and their associations with key organizational and individual factors. Data were analysed using descriptive statistics, chi-square tests, and logistic regression to identify significant relationships and prevalence rates. The findings showed that 73.5% of nurses were satisfied with their jobs, while 20.1% reported an intention to leave. Job satisfaction was positively associated with supportive organizational policies, a positive work environment, higher patient care quality, and individual characteristics. Turnover intention was lower compared to global benchmarks, suggesting the potential impact of favourable workplace practices and systems in the UAE. Enhancing job satisfaction and reducing turnover intention require supportive policies, positive work environments, and access to professional development opportunities.